The Open Innovation Strategies towards Learning Effectiveness in Education Industry: with Special Reference to Sri Lanka - Gunarathne, Inoka (Archives of Business Research, 2019)
Digital transformation is a significant disruptor in education industry. Growing concerns arise in terms of adoption of technology by education industry due to disruption. The current study is focused to assess the adoption of open innovation strategies to learning effectiveness in education industry with special reference to Sri Lanka. The study consisted of 115 respondents studying in various disciplines in a range of programs such as Diploma, HND, Degree and Postgraduate programs. The participation in the experiment by the each unit was voluntary and no monetary reward was offered for taking part. The learning effectiveness was measured using portfolio - dossier profile developed by O’Neil and Wright. The empirical evidence support the hypothesis indicating a positive correlation to exist. The study reveals that the Sri Lankan education industry institutions should make use of open innovation strategies in for effectives in learning performance of students. The results of the study offer implications for industry players to rethink about their educational offerings and to consider the way in which the entire business model is organized. Thus, the players in the industry must incorporate a curriculum that facilitate active learning strategies to use by learners. Further, the institution should make use of new technology, facilitate the ability of a learner to set the learning pace and make the learner understand the outcomes of learning at the beginning of his or her learning for improved learning effectiveness.